Involvement of Ocular Muscles in Patients With Myasthenia Gravis With Nonocular Onset. Issue 1 (March 2022) - Lei, Lin; Fan, Zhirong; Su, Shengyao; Xu, Min; Chen, Hai; Zhu, Wenjia; Luan, Qinrong; Da, Yuwei
Abstract : Background: Myasthenia gravis (MG) is an autoimmune disorder involving neuromuscular junctions and more than half of MG patients manifested with extraocular muscle weakness initially. In the remained patients, ocular weakness may occur later in the course of the disease. However, little data are available about ocular involvement in such patients. Therefore, the study aims to investigate ocular weakness in MG patients with nonocular onset and evaluate the associated factors influencing it. Methods: In our monocentric retrospective study, 54 adult-onset patients with MG with nonocular onset were included and were followed up for at least 2 years from the onset. The primary outcome was the occurrence of ptosis, diplopia, or both. Kaplan–Meier analysis was performed to estimate the time to the ocular weakness, and log-rank tests were used to analyze the association between clinical characteristics and ocular weakness. Multivariate Cox proportional hazards regression models were used to identify factors associated with ocular involvement. Results: A total of 47 (87.0%) patients developed ocular weakness during the study period. The median time to ocular weakness was 6.0 months. Time to the ocular involvement was earlier in patients with bulbar onset ( P = 0.007), whereas patients receiving pyridostigmine monotherapy and immunomodulatory therapy had a longer median time of ocular weakness ( P < 0.0001). No significant difference was noted between ocular weakness and age of onset, gender, and thymoma. The Cox analysis showed that bulbar onset was a risk factor of ocular weakness (adjusted hazard ratio [HR] 2.65, 95% confidence interval [CI] 1.41–4.99), whereas pyridostigmine monotherapy (adjusted HR 0.28, 95% CI 0.13–0.60) and immunotherapy (adjusted HR 0.09, 95% CI 0.04–0.22) were protective factors. Conclusions: Eighty-seven percent of patients with MG with nonocular onset developed ocular weakness. Bulbar onset was an independent risk factor for ocular involvement, whereas pyridostigmine and immunotherapy were protective factors.